Neurological sequelae in a patient with previous neurocysticercosis - Onuki, Maria Eduarda (2022)
Introduction Teniasis and cysticercosis are caused by the platelminth Taenia solium, a parasite that has in its cycle the pig and man. Teniasis occurs with the ingestion of raw or undercooked contaminated pork containing cysticercus. On the other hand, human cysticercosis occurs through ingestion of T. solium eggs through fresh vegetables, raw meat or contaminated water, in the body, the larvae migrate and acquire the cystic form, usually in the host's muscle tissue.Neurocysticercosis (NCC) develops when the invasion of the larvae occurs in the human central nervous system, found in the nervous tissue or in the intraventricular, subarachnoid, and spinal cord spaces, where there is circulation of CSF, leading to different clinical manifestations and prognosis. Objective To report the case of a patient with NCC with neurological complications at IIER. Case description Female, 37 years old, carrier of Diabetes Mellitus type 2 (DM2), migraine and structural epilepsy. She has a previous history of rheumatic fever in childhood and NCC since 2001, contracted when she lived in the interior of Bahia where she raised pigs and ate this meat, treated at IIER in May/2019. A headache associated with absence and vertigo crises began in October/2020 as consequences of NCC, reasons for which the patient was hospitalized and later referred to the neurology outpatient clinic, after CSF analysis without evident alterations.The patient was admitted to the IIER with a history of intermittent vertigo for 2 days and shooting headache in the right frontal region of the skull, in addition to the return of absence seizures until then extinct since the last hospitalization in October/2020, accompanied by the neurologist physician who increased valproic acid from 1.25g to 1.5g a day, also reported that this time, presents very significant worsening of vertigo. (To see the complet abstract, please, check out the PDF.)